Calculation of the Photons Emission Rate by Interaction of Charm Quark with Gluon - Ridha, Ola; Shweikh , Ahmed M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
In this paper, a theoretical model has been presented to calculate the rate of photon emission. The photonic yield has been calculated for the interaction of heavy charm quarks with gluon from Bremsstrahlung processes. The rate of photon emission was evaluated for the interaction of the charm quarks with the gluons